A genome-wide study on gene–nutrient interactions for hyperuricemia in a large Korean cohort (KoGES) - Ehn-Young Kim; Ja-Eun Choi; Ji-Won Lee; Jae-Min Park; Youhyun Song; Yu-Jin Kwon; Kyung-Won Hong (Scientific Reports)
Abstract This study aimed to identify novel genetic variants associated with hyperuricemia risk across multiple nutrients by assessing significant gene–nutrient interactions using large-scale genome-wide association study (GWAS) data in the Korean population. A total of 48,007 individuals from the Korean Genome and Epidemiology Study dataset were included in the GWAS. Dietary intake was evaluated using a food frequency questionnaire. To identify genomic loci that interact with specific nutrients influencing hyperuricemia risk, we conducted a GWAS followed by gene–nutrient interaction analyses of genome-wide significant single-nucleotide polymorphisms (SNPs). Two SNPs with significant gene–nutrient interactions for specific nutrients were identified: rs113206751 in the Membrane-Associated Ring-CH-Type Finger 1 (MARCH1) gene and rs9393235 in the Neuroblastoma-Associated Transcript 1 (NBAT1) gene near the prolactin (PRL) gene. Among individuals consuming vitamin A above the dietary reference intake (DRI), carriers of the minor allele (A) at MARCH1-rs113206751 had a higher risk of hyperuricemia than those with the reference allele (-, no insertion) (odds ratio [OR] 1.63, 95% confidence interval [CI] 1.38–1.93, p: 1.01 × 10− 8, interaction p: 1.22 × 10− 6). Among individuals consuming potassium above the DRI, carriers of the minor allele (G) at NBAT1/PRL-rs9393235 showed an increased risk of hyperuricemia than those with the reference allele A (OR 3.14, 95% CI 2.09–4.71, p: 3.69 × 10− 8, interaction p: 1.21 × 10− 5). These findings suggest potential gene–nutrient interactions between MARCH1 and vitamin A, as well as between NBAT1/PRL and potassium, in relation to hyperuricemia risk. However, these findings may have limited generalizability beyond the Korean population studied and require validation in more diverse populations. This study emphasizes genomic-nutritional integration for personalized hyperuricemia management.